An empirical study of supporting executive function in family education with mental abacus - Watanabe, Nobuki (Frontiers in Education, 2023)
In the field of childcare, the focus has primarily been on executive function (EF) (working memory [WM]), which is a critical factor in daily life. The Wechsler Intelligence Scale for Children’s (WISC-IV) WM Index subtests of the digit span (forward and backward) and letter–number sequencing tasks are used to assess EF (WM). Theoretically, the letter–number sequencing task is more demanding on EF (WM) than the digit span task. Additionally, there is some suggestion of a relationship between EF (WM) and mental abacus (MA) and that MA can easily be performed in daily life. One challenge of supporting EF (WM) is that it is hard to conduct general evaluations and daily activities at home. This study examines the following questions through an empical study: (1) Can Mental Abacus be used to support executive function in family education? In this study, I measured the cerebral blood flow of one child at home using the HOT-2000 for the tasks of MA and the WISC-IV. As a result, I was able to show that for that child, MA could have an effect on EF(WM). Although this is only one example, for parents, it has been important in showing that it is not impossible in the field of home education where there are many different kinds of children. The findings provide a new perspective regarding evaluating EF (WM) in cognitive psychology and neuropsychology and are valuable in breaking through previous research.